Nativisation of Arabic names: the Yoruba language as a case study (2014)
One unique characteristic feature of the Yoruba language, spoken in South Western Nigeria is that when words are borrowed into it from other languages, such words are nativised. Some scholars have discussed the rules that apply in such cases. However, this kind of study has not been extended to Arabic names borne by Yoruba people (to the best of my knowledge). This paper therefore discusses the rules that apply on some of these names. Thirty Arabic names are purposively selected for discussion here. The theoretical framework adopted is natural phonology which operates with phonological processes that are deemed to constitute natural responses of human vocal and perceptual systems to the difficulties encountered in the production and perception of speech. Yoruba speakers apply some phonological rules on Arabic names in an attempt to make them conform to the syllable patterns of the Yoruba language. Vowel insertions of two kinds take place. The first kind is epenthetic in nature, because it involves the insertion of an extra medial vowel to break consonant clusters. The other kind takes place at the word final position. This is done to prevent consonants from ending names since the Yoruba syllable structure is essentially an open one